THE EFFECT OF DIRECTED READING THINKING ACTIVITY (DRTA) LEARNING STRATEGY AND READING INTEREST FOR READING COMPREHENSION ABILITY - Annida, Arini Itsna; Slamet, St. Y.; Winarni, Retno (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This research is intended to find the different of reading comprehension ability of student that teached by teaching Directed Reading Thinking Activity (DRTA) learning strategy within Know-Want to Know-Learned (KWL) learning strategy, the different of reading comprehension ability of student that have the high reading interest and low reading interest, and the interaction between learning strategy and studied reading interest on the reading comprehension ability. This study was a quasi experimental research methode design by 2×2 factorial design. Population of the research are all student at fifth grade of elementary school in Laweyan district Surakarta in the academic year of 2017/2018. Samples were taken by cluster random sampling technique. The selected sample are Pajang 1 elementary school and Karangasem 1 elementary School. The data collecting uses test and non test technique. This research used two ways anava data analysis technique and used Scheffe method as a further testing after two ways anova with 5% of significance level. The result of research shows that a different of reading comprehension ability of student that teached by Directed Reading Thinking (DRTA) learning strategy within Know-Want to Know-Learned (KWL) learning strategy, there was a different of reading comprehension ability of student that have the high reading interest and low reading interest, and there was an interaction between learning strategy and reading interest on the reading comprehension ability.